Analysis of glutathione S-transferase (M1, T1 and P1) gene polymorphisms in Iranian prostate cancer subjects - Basir, Sahar Ansari; Vasudevan, Ramachandran; Bakhshi, Ali; Mirinargesi, Mirsaed; Ismail, Patimah; Abdul Rahman, Sabariah; Pasalar, Parvin (Academic Journals, 2010)
Glutathione S-transferase enzymes are active in detoxifying a wide number of endogenous and exogenous chemical carcinogens and subsequently, are crucial in protecting the DNA. Several studies show some differences in association of glutathione S-transferase M1, T1 and P1 genetic polymorphisms with the risk of prostate cancer in various populations. The current study was done with Iranian subjects to evaluate the association of the polymorphism of glutathione S-transferase subtypes (T, M and P) and the susceptibility of prostate cancer in Iranian patients as compared to controls. Blood samples were collected from 65 prostate cancer patients and 65 unrelated health individuals as controls from Milad hospital, Tehran, Iran. The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used to determine the polymorphism of glutathione S-transferase pi (GSTP1) -313 A/G gene, while multiplex PCR method was utilized to detect the glutathione S-transferase teta (GSTT) 1 and glutathione S-transferase mµ (GSTM) 1 null allele. There was no significant association in the -313 G allele (Val) of GSTP1 gene polymorphism and prostate cancer risk (odds ratio 0.61, 95% confidence intervals (CI) 0.08 -4.60, p = 0.627). Moreover, no relationship was found between the polymorphism of GSTT1 (odds ratio 0.66, 95% CI 0.27 -1.62) and GSTM1 (odds ratio 0.54, 95% CI 0.27 -1.08) genes and higher risk of prostate cancer among Iranian subjects (p > 0.05). This study showed that either GSTP1-313 G polymorphism or GSTT1 and GSTM1 genes cannot be predisposing risk factors for prostate cancer among Iranian subjects.